Penerapan Model Pembelajaran Kooperatif Tipe Rotating Trio Exchange pada Materi Turunan Fungsi - Rika Handayani (Departement of Mathematics Education, 2023)
This study aims to determine the learning outcomes through the RTE type cooperative learning model on Derivative Functions material and to determine student responses to the RTE type cooperative learning model. The approach used is a quantitative approach. The type of research is experimental research with a one-shot case study design. The population of all students of class XI SMA Negeri 3 Banda Aceh, the sample was taken randomly as much as 1 class, namely class XI IPA. Data collection techniques are carried out by carrying out learning outcomes tests. Data processing is done by testing the Run Test. The conclusion that can be drawn is that